Direct intermolecular three-component aminotrifluoromethylation of styrenes by visible-light-photoredox catalysis. Issue 23 (12th October 2022) - Zheng, Lvyin; Cai, Liuhuan; Zhuo, Xiaoya; Deng, Lei; Wu, Yingying; Yang, Beining; Wang, Yihan; Guo, Wei
Abstract : A visible-light-photoredox-catalyzed intermolecular three-component aminotrifluoromethylation of styrenes with phenylhydrazines and Togni's reagents/fluoroalkyl iodides was developed. Abstract : Reported herein is a visible-light-photoredox-catalyzed intermolecular three-component aminotrifluoromethylation of styrenes with phenylhydrazines and Togni's reagents/fluoroalkyl iodides. This synthetic strategy utilizes phenylhydrazines as nitrogen sources, and Togni's reagent or various fluoroalkyl iodides as fluorine sources. This approach involves the direct and regioselective formation of new C–N/C–C bonds and the cleavage of an N–N bond in one pot. The reaction mechanism was probed by radical-trapping, fluorescence quenching, cyclic voltammetry, and light on/off experiments. This transformation was shown to feature the merits of being operationally simple, with good functional group tolerance, and can be carried out under mild conditions, and can be further applied to the late-stage structural modification of bioactive pharmaceuticals for medicinal chemistry.